2020
DOI: 10.1186/s13148-020-00882-w
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of cg05575921 demethylation response in nascent smoking

Abstract: The initiation of adolescent smoking is difficult to detect using carbon monoxide or cotinine assays. Previously, we and others have shown that the methylation of cg05575921 is an accurate predictor of adult smoking status. But the dose and time dependency of the demethylation response to smoking initiation in adolescents is not yet well understood. To this end, we conducted three consecutive annual in-person interviews and biological samplings of 448 high school students (wave 1 (W1)-wave 3 (W3)). At W1 (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
1
14
1
Order By: Relevance
“…Our methylation levels for cg05575921 were similar to previous reports realized in different populations with tobacco consumption [20,25,32,62,63] and non-smokers [25,63], showing replicable results in most populations studied; this is relevant because, previously, cg05575921 has been proposed as a biomarker of smoking status since DNA methylation is not affected by short-term abstinence periods [32].…”
Section: Discussionsupporting
confidence: 89%
“…Our methylation levels for cg05575921 were similar to previous reports realized in different populations with tobacco consumption [20,25,32,62,63] and non-smokers [25,63], showing replicable results in most populations studied; this is relevant because, previously, cg05575921 has been proposed as a biomarker of smoking status since DNA methylation is not affected by short-term abstinence periods [32].…”
Section: Discussionsupporting
confidence: 89%
“…In that study, on the presumption that most high school sophomores will not yet have started smoking, we enrolled 15 year-old high school students and followed them for two years, drawing their blood and measuring their CO levels at three points of time. In the 364 subjects who denied any type of smoking and had negative cotinine and cannabinoid levels, the average level of cg05575921 methylation at age 15 using this assay was 86.8% ± 3.2 22 . That is very similar to the 86.6% ± 2.9 found in these 423 biochemically screened adults and strongly argues against any significant age dependent changes in cg05575921 methylation in adult subjects.…”
Section: Discussionmentioning
confidence: 95%
“…To address these challenges and establish the methylation set points of cg05575921 methylation, we have surveyed populations with low likelihood of significant underreporting to get a better understanding of the assay set point in various groups. The most notable effort prior to this communication has been the Healthy Iowan Study 22 . In that study, on the presumption that most high school sophomores will not yet have started smoking, we enrolled 15 year-old high school students and followed them for two years, drawing their blood and measuring their CO levels at three points of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in the field of epigenetics may offer a means of overcoming some limitations of current smoking biomarkers. In particular, multiple studies and meta-analyses ( 27 , 32 , 33 ) have shown that decreased methylation of the genomic CpG cg05575921, located in the gene Aryl Hydrocarbon Receptor Repressor ( AHRR ), is a strongly performing biomarker for cigarette (AUC = 0.99) ( 34 ) that is both sensitive to light smoking ( 35 ) and demonstrate dose-response characteristics ( 34 , 36 , 37 ).…”
Section: Introductionmentioning
confidence: 99%